Performance comparison between analytical analysis and numerical simulations for average soliton system - Zakaria, Zahariah (2011)
This paper presents the comparison between analytical results and computer simulated results showing the performance of soliton transmission in optical fibre optics . A study of average soliton systems with 50 km amplifier spacing is presented both analytically and numerically. The effect of modifying the existing rule of thumb formulae is presented in terms of a design diagram. Th is is then compared to the numerical simu lations. A series of design diagram with Gordon-Haus (GH) jitter, signal to noise ratio (SNR) and soliton collapse limited transmission is also introduced.